Association between prognostic nutritional index and long-term mortality in intensive care unit patients with pressure ulcers: A retrospective study - Yamin Bo; Chao Song; Jinhui Zhang (PLoS ONE, 2026)
Background The prognostic nutritional index (PNI), an integrated marker of nutritional and immune status, has been proposed as a potential prognostic factor in critically ill patients. This study aimed to investigate the relationship between PNI and long-term mortality in intensive care unit (ICU) patients with pressure ulcers. Methods Individuals with pressure ulcers were selected from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database and divided into four categories according to the quartiles of the PNI. Several statistical methods were employed to evaluate the association between PNI and long-term mortality, including Kaplan-Meier survival analysis, multivariable Cox proportional hazards models, restricted cubic splines (RCS), receiver operating characteristic (ROC) curves, and subgroup analyses. Results The median age of the 796 participants was 70.33 years (IQR: 60.91–79.96), with 451 (56.7%) being male. During the follow-up period, 476 patients (59.8%) died within 365 days, and 413 patients (51.9%) died within 180 days. Kaplan-Meier analysis indicated that patients with elevated PNI values had a significantly lower risk of mortality at both 365 and 180 days. After full adjustment for potential confounders, patients in the highest PNI quartile had significantly lower mortality risks compared to those in the lowest quartile (365-day mortality: HR = 0.598, 95% CI: 0.455–0.786, P < 0.001; 180-day mortality: HR = 0.558, 95% CI: 0.414–0.753, P < 0.001). A non-linear L-shaped relationship was identified between PNI and mortality, with threshold values of 28.45 for 365-day mortality and 29.15 for 180-day mortality. Conclusions A lower PNI was significantly associated with increased risk of long-term mortality in ICU patients with pressure ulcers. These findings suggested the potential of PNI as a valuable prognostic biomarker in this population.